(untitled) (American Journal of Islam and Society, 1989)
During the recent past a number of Muslim psychologists in Pakistan as well as other countries have attempted to develop a greater understanding of basic Islamic sources for an alternate view of human psyche. This is an approach which is quite new for psychologists in Muslim countries who have been trained in the Western intellectual tradition, and have depended on Western sources for their methods, models and content areas of research. Since the Qur’an is the basic source of Islamic thought, it is not surprising that a number of Muslim psychologists have turned to the Qur’an in order to develop an alternate perspective of understanding the human psyche. It was therefore proposed that the IIIT should help in consolidating the efforts being made in this respect by sponsoring a seminar for psychologists interested in this area. Objectives The seminar aimed at giving the Pakistani psychologists interested in the application of Islamic concepts in understanding human psyche an opportunity to meet and exchange ideas, and to present their views and findings to each other and to teachers and advance students of psychology. The Seminar The seminar was organized by the IIIT, Pakistan in collaboration with the Department of Psychology, Government College, Lahore. This department, which is the oldest institution of post-graduate teaching and research in psychology in Pakistan, has a strong tradition of interest in Muslim Psychology. They offer an optional course in Muslim Contributions to Psychotherapy also. The local organizer was Dr. Azhar Ali Rizvi, Chairperson of the above department. The seminar was held on April 3, 1989 in Falleties Hotel, Lahore. In all, 21 persons attended the delibemtions. They included eminent psychologists, social scientists and some scholars of the Holy Qur‘an. Apart from the kkhtani participants, two psychologists from Dhaka University, Bangladesh read their ...